Ventilación mecánica en paciente con traumatismo craneoencefálico severo de sexo masculino de 63 años de edad. - Troya Crespo, Elva Dayana (2020)
The present case study deals with a 63-year-old male patient with a personal pathological history of hypertension; suffered a traffic accident, suffering multiple trauma, cranioencephalic trauma accompanied by loss of consciousness, he was transferred to the nearest General Hospital, where he was admitted with cervical immobilization, on a rigid table and with a Glasgow score of 8. Physical examination found a blunt trauma in right parietal region with depressed fracture thicker than skull thickness; multiple abrasions and open fracture of the right forearm. It was decided to intubate and maintain 100% oxygenation, through mechanical ventilation. The skull tomography reported a right parietal fracture with the formation of a large epidural hematoma and he was operated on, then he was transferred to the intensive care unit in critical condition, he convulsed on several occasions, despite the indicated therapy, his vital signs decreased gradually and died 6 hours after surgery. The objective of this study is to analyze, through the case study methodology, mechanical ventilation in a 63-year-old male patient with severe head injury. In the ventilatory action in patients with head trauma, it should be aimed at avoiding hypoxia, maintaining a PaO2> 60 mmHg; recommending normocapnia with PaCO2 between 35–45 mmHg and the use of positive pressure at the end of expiration if necessary